Studi Karakteristik dan Model Pemilihan Moda Angkutan Mahasiswa Menuju Kampus di Universitas Lampung - Habibi, Naufal; Purba, Aleksander; Herianto, Dwi (Universitas Lampung, 2019)
The University of Lampung is one of university in lampung that possesses the active as much as 25.805 students in 2016. This study aims to for any identifying characteristic mode of transportation and he knows the selection of factors influencing the students in an election mode of transportation to campus .This study was conducted by the use of the method of analysis descriptive against characteristic of the selection of modes of transportation by college students and methods correlations to know variables affecting the selection of modes of transport by university students lampung.The result of this study showed that the proportion of students foot and bike (16,7%) percent motorcycle (48,0%) percent car (16,0%) percent and public transportation (19,3%) percent The results of the testing correlation value and the relationship with the variables transportation used by students to reach campus and unknown factors influencing the selection of modes of transportation students to campus University of Lampung, sex is the intensity of the, mode the cost of /, fare, age travel time, mileage, vehicle ownership and income parents based on the calculation on a variable that has the lowest correlation value are ownership variables license with the correlation of 0,180 (α<0,05), and the highest correlation is variable income parents with the correlation of 0,398 (α< 0,05).